2010
DOI: 10.1038/oby.2009.501
|View full text |Cite
|
Sign up to set email alerts
|

JNK Deficiency Enhances Fatty Acid Utilization and Diverts Glucose From Oxidation to Glycogen Storage in Cultured Myotubes

Abstract: Although germ‐line deletion of c‐Jun NH2‐terminal kinase (JNK) improves overall insulin sensitivity in mice, those studies could not reveal the underlying molecular mechanism and the tissue site(s) in which reduced JNK activity elicits the observed phenotype. Given its importance in nonesterified fatty acids (NEFA) and glucose utilization, we hypothesized that the insulin‐sensitive phenotype associated with Jnk deletion originates from loss of JNK function in skeletal muscle. Short hairpin RNA (shRNA)–mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…This finding suggests the possibility that promotion of steatosis by JNK1 is mediated through an effect other than that on insulin resistance, as loss of JNK2 failed to affect lipid accumulation despite significantly improving insulin sensitivity. The absence of an effect on hepatic lipid accumulation in vivo is in contrast to findings in adipocytes and muscle cells in which JNK2 inhibition increased β-oxidation and lipolysis, respectively [52,53]. This discrepancy may reflect an artifact of the in vitro studies in the non-hepatic cells or the tissue-specific nature of JNK regulation of lipid metabolism.…”
Section: Mechanisms Of Jnk Regulation Of Steatosis and Hepatitismentioning
confidence: 80%
See 1 more Smart Citation
“…This finding suggests the possibility that promotion of steatosis by JNK1 is mediated through an effect other than that on insulin resistance, as loss of JNK2 failed to affect lipid accumulation despite significantly improving insulin sensitivity. The absence of an effect on hepatic lipid accumulation in vivo is in contrast to findings in adipocytes and muscle cells in which JNK2 inhibition increased β-oxidation and lipolysis, respectively [52,53]. This discrepancy may reflect an artifact of the in vitro studies in the non-hepatic cells or the tissue-specific nature of JNK regulation of lipid metabolism.…”
Section: Mechanisms Of Jnk Regulation Of Steatosis and Hepatitismentioning
confidence: 80%
“…An adenovirus-mediated knockdown of JNK1 in mouse liver not only improved insulin sensitivity but also upregulated genes involved in glycolysis, triglyceride secretion and β-oxidation [51]. Recent studies have also demonstrated that blocking JNK function increases fatty acid oxidation in muscle [52], so the possibility that JNK inhibition has a beneficial effect on steatosis by increasing fatty acid utilization in the liver or other organs needs further investigation.…”
Section: Mechanisms Of Jnk Regulation Of Steatosis and Hepatitismentioning
confidence: 99%
“…The next step of our study was to investigate how α‐LA could up‐regulate PPARβ expression. Because it was known that α‐LA could affect the JNK pathway (12) and that expression regulation of genes involved in fatty acid metabolism depends on both the activity of JNK and PPARβ pathway (13), we decided to examine the activity of the JNK pathway. Based on Western blot analysis, the JNK pathway appears to be activated in C2C12 cells in basal conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, α‐LA has been shown to lower in C2C12 myotubes the activation of the JNK pathway (12). It is noteworthy that this pathway is involved in the down‐regulation of genes that regulate fatty acid oxidation (13). Moreover, transcription of fatty acid oxidation genes is known to be controlled by the peroxisome proliferator‐activated receptor (PPAR)b, a transcription factor highly expressed in the skeletal muscle of physically trained individuals and rodents (14).…”
mentioning
confidence: 99%
“…In obese mice, muscle could therefore be a site of JNK1 function, regulating insulin sensitivity and glucose homeostasis. Indeed, shRNA-mediated knock-down of JNK in cultured myotubes causes increased fatty acid oxidation and increased conversion of glucose to the storage form glycogen [60]. …”
Section: Muscle Jnk1 Regulates Insulin Resistancementioning
confidence: 99%